Tren Pelatihan Pembelajaran Jarak Jauh (PJJ) Sebelum dan Semasa Pandemi Covid-19 - Khoirunnisa Khoirunnisa; Suci Hayati (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2023)
Abstract:Â The Covid-19 pandemic has had a real impact on various aspects including in the trend of research publication topics related to Distance Learning Training (PJJ Training) and Higher Education Distance Learning (PJJ PT) which has increased sharply. The objectives of this study are to: 1) describe the publication trends of PJJ training and PJJ PT, and 2) analyze the types of scientific publications, research approaches and methods, research subjects, and research links to extension. This research approach is mixed method with Systematic Literature Review (SLR) method using the help of Publish or Perish (PoP) program, Vos Viewers and Microsoft Excel. The results showed that: 1) the trend (tendency) of the number of publications related to Distance Learning Training is more than publications related to Higher Education Distance Learning, especially during the Covid-19 pandemic with a peak in the number of publications in 2021 which reached 512 articles, 2) the type of scientific publications used as a place of publication is more in community service or PKM journals (58.33%) than journal articles (41.67%); the approaches used by at least 10% are qualitative (10.71%), quantitative (10.71%), training and mentoring (15.48%), training and workshops (20.24%) and training and tutorials (26.19%) with direct methods (51.19%), indirect methods (29.76%) while the rest are spread over various other methods; the majority of research subjects on the topic of distance learning training are teachers (71.43%), while a small proportion of subjects on both topics consist of students (9.52%), college students (7.14%), lecturers (4.76%), and the rest are spread on other subjects; and publications on the topic of distance learning training have a strong relationship with training and counseling (96.00%), while publications on the topic of college distance learning have less strong relationship with training and counseling (11.11%).Abstrak:Â Pandemi Covid-19 berdampak nyata pada berbagai aspek termasuk dalam tren topik publikasi hasil penelitian terkait Pelatihan Pembelajaran Jarak Jauh (Pelatihan PJJ) dan Pembelajaran Jarak Jauh Peguruan Tinggi (PJJ PT) yang meningkat tajam. Tujuan penelitian ini untuk: 1) mendeskripsikan tren publikasi pelatihan PJJ dan PJJ PT, dan 2) menganalisis jenis terbitan ilmiah, pendekatan dan metode penelitian, subyek penelitian, dan kaitan penelitian dengan penyuluhan. Pendekatan penelitian ini adalah campuran (Mixed Method) dengan metode Systematic Literature Review (SLR) menggunakan bantuan program Publish or Perish (PoP), VosViewers dan Microsoft Excel. Hasil penelitian menunjukkan bahwa: 1) tren (kecenderungan) jumlah publikasi terkait Pelatihan Pembelajaran Jarak Jauh lebih banyak dibandingkan dengan publikasi terkait Pembelajaran Jarak Jauh Perguruan Tinggi terutama semasa pandemi Covid-19 dengan puncak peningkatan jumlah publikasi tejadi pada tahun 2021 yang mencapai 512 artikel, 2) jenis terbitan ilmiah yang dijadikan tempat publikasi lebih banyak di jurnal pengabdian masyarakat atau PKM (58,33%) daripada jurnal artikel (41,67%); pendekatan yang digunakan minimal 10% adalah kualitatif (10,71%), kuantitatif (10,71%), pelatihan dan pendampingan (15,48%), pelatihan dan workshop (20,24%) dan pelatihan dan tutorial (26,19%) dengan metode langsung (51,19%), metode tidak langsung (29,76%) sementara sisanya menyebar pada berbagai metode lain; mayoritas subjek penelitian topik Pelatihan PJJ adalah guru (71,43%), sementara sebagian kecil subjek pada kedua topik terdiri dari siswa (9,52%), mahasiswa (7,14%), dosen (4,76%), dan sisanya menyebar pada subjek lainnya; dan publikasi topik pelatihan pembelajaran jarak jauh memiliki keterkaitan yang kuat dengan pelatihan dan penyuluhan (96,00%), sementara publikasi topik pembelajaran jarak jauh perguruan tinggi kurang memiliki keterkaitan yang kuat dengan pelatihan dan penyuluhan (11,11%).